Hydrothermal synthesis of organometal halide perovskites for Li-ion batteries1. Issue 72 (18th September 2015) - Xia, Hua-Rong; Sun, Wen-Tao; Peng, Lian-Mao
<x xml:space="preserve">Abstract</x> A facile rapid hydrothermal method was developed to prepare CH3NH3PbBr3 and CH3NH3PbI3. The as-prepared products were utilized in lithium batteries as anode materials with good performance. Considering the structural diversity, more hybrid perovskites can be targets for further optimization, indicating their promising potential in Li-ion battery applications.